2017
DOI: 10.1038/nrcardio.2017.161
|View full text |Cite
|
Sign up to set email alerts
|

The NLRP3 inflammasome in acute myocardial infarction

Abstract: The heart is extremely sensitive to ischaemic injury. During an acute myocardial infarction (AMI) event, the injury is initially caused by reduced blood supply to the tissues, which is then further exacerbated by an intense and highly specific inflammatory response that occurs during reperfusion. Numerous studies have highlighted the central role of the NACHT, LRR, and PYD domains-containing protein 3 (NLRP3) inflammasome in this process. The inflammasome, an integral part of the innate immune system, is a mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
388
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 537 publications
(400 citation statements)
references
References 92 publications
5
388
0
7
Order By: Relevance
“…However, the potential role of H19 in AMI is still far from clear. Inflammation and apoptosis are two crucial factors that contribute to AMI and the subsequent cardiac remoulding . Interestingly, investigators have verified that H19 is a key mediator involved in myocardial inflammatory reactions and apoptosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the potential role of H19 in AMI is still far from clear. Inflammation and apoptosis are two crucial factors that contribute to AMI and the subsequent cardiac remoulding . Interestingly, investigators have verified that H19 is a key mediator involved in myocardial inflammatory reactions and apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the most effective strategy for the treatment of AMI mainly focuses on timely reperfusion of the ischaemic myocardium by dissolving the thrombus with medications or percutaneous coronary intervention . Although these strategies are effective in limiting heart injury and reducing infarct size, patients with AMI remain at increased short‐term and long‐term risk of heart failure, and only approximately half of patients survive for 5 years or longer after diagnosis . Therefore, therapeutic approaches that could alleviate progressive maladaptive cardiac remodelling and improve heart performance in the long run are still the Holy Grail of this field.…”
Section: Introductionmentioning
confidence: 99%
“…1 To combat this profile of progressive cardiac deterioration after ischemic injury, cell-specific approaches have emerged with emphasis on altering the hematopoietic response, 2 ameliorating fibrotic remodeling, 36 increasing collateral circulation, 7,8 and preserving or replacing cardiomyocytes. 9,10 Earlier reports that endogenous cardiac stem cells exist and might be efficacious in mediating cardiac regeneration generated a great deal of excitement in the field.…”
mentioning
confidence: 99%
“…In 80 patients with RA and with (n=20) or without coronary artery disease (n=60), anakinra reduces oxidative stress and improved left ventricular contractility and relaxation as measured by tissue Doppler echocardiography 8. Anakinra also appears to improve cardiorespiratory fitness in patients with systolic HF 6. A recent large phase III clinical trial of IL-1β in patients with prior acute myocardial infarction showed reduced recurrent cardiovascular events as well as reduced incidence of arthritis, further strengthening this link 9…”
mentioning
confidence: 95%
“…Each of these cytokines, independently and synergistically, can induce a reversible myocardial dysfunction. Members of the IL-1 family of cytokines, IL-1β and IL-18, have been identified as soluble cardiosuppressant factors also in acute decompensated HF 6. TNF-α and IL-1β may not be interchangeable and their regulatory system and signalling cascade are only minimally overlapping.…”
mentioning
confidence: 99%